Quantum Dot‐in‐Mechanoluminescent Matrix for Full‐Color Implementation. Issue 2 (15th November 2022) - Jeong, Hong In; Yang, Jonghee; Jeong, Woo Hyeon; Oh, Jae Taek; Song, Hochan; Lim, Seul Gi; Ha, Su Ryong; Lee, Bo Ram; Seo, Hyo Jin; Choi, Hyosung
Abstract: Mechanoluminescence (ML), a novel process that converts mechanical momentum to light emission, has shown potential for sustainable future technologies. However, the lights emitted from classical ML materials have shown broad emission spectra and a limitation in the choice of colors so far, constraining the full‐color implementation of ML. Herein, a quantum dot (QD)‐in‐mechanoluminescent matrix (QMM) architecture is introduced by simply incorporating QDs with the classical ML‐active matrices, designed to utilize the sharp emission spectra of the QDs. The QMMs demonstrate distinctive green and red lights identical to the emissions from the QDs through mechanical stimuli, achieving the purest ML reported to date. Furthermore, the deployments of the QDs allow the full‐color implementation of ML covering a wide color gamut, as well as the demonstration of the purest white reported to date. Systematic investigations reveal that the ML operation in the QMM is governed according to the ML‐stimulated photoluminescence (PL) mechanism, preventing energy or charge transfer processes. Moreover, the QMMs exhibit excellent stabilities upon environmental stresses and the patterned system is readily prepared, guaranteeing both robustness and easy processability of the system. This simple QMM strategy suggests practical insights for the development of powerless ML display and lighting systems. Abstract : Quantum dot (QD)‐in‐mechanoluminescent matrix architecture demonstrates pure red/blue/green and white color emission light that covers a wide range of the color gamut only by mechanical stimuli, deploying high spectral/color accuracy and purity of finely tuned bandgap of the QDs. This strategy suggests practical insights for the development of color‐pure and eco‐friendly lighting systems, contributing to sustainable future applications.